Dampak Positif Fitokimia Zeaxanthine Terhadap Kesehatan Mata dan Penyakit Degeneratif - Rahma Wulaningrum (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Degenerative diseases such as diabetes mellitus are related to eye health. This is because the blood vessels in the retina can be an indication when someone is experiencing a pathological abnormality. Zeaxanthine as a type of phytochemical which is included in the carotenoid group or derivative has a role in preventing eye damage, especially to the retina and several degenerative diseases. This research uses a literature review method by retrieving scientific articles online on trusted pages such as PubMed, Science Direct and Crossmark. The aim of this research is to determine the effect and benefits of consuming zeaxanthin either in the form of consuming food sources of zeaxanthin directly or through supplements on eye health and degenerative diseases. The results of this study show the positive role of zeaxanthin in maintaining eye health and preventing nearsightedness, retinal damage and cataracts. Meanwhile, the relationship between zeaxanthin intake and the prevention of degenerative diseases has been explained in all scientific articles used in this research.